Soil and water conservation treatment have a significant effect on value of C factor and soil erosion. Vegetatif conservation treatment aimed to reduce of both C factor and soil erosion of the cacao cropping system. The decrease of both C factor and soil erosion were affected by density of crop canopy and plant rows in counter line, with organic matter addition from system mentioned above. Experimental method with field study was applied in split plot design consisting three factors, namely ( - Nurmi Hafid; Oteng Haridjaja; Sitanala Arsyad; Sudirman Yahya (Forum Pasca Sarjana, 2008)
Soil and water conservation treatment have a significant effect on value of C factor and soil erosion.  Vegetatif conservation treatment aimed to reduce of both C factor and soil erosion of the cacao cropping system.  The decrease of both C factor and soil erosion were affected by density of crop canopy and plant rows in counter line, with organic matter addition from system mentioned above.  Experimental method with field study was applied in split plot design consisting three factors, namely (i) slope consisting two levels (10-15% and 40-45%) and (ii) age of the cacao plant consisting two levels (5 to 7 month and 25 to 27 month) were used as main plots (P1 = 5 to 7 month and 10-15%; P2 = 25 to 27 month and 10-15%; P3 = 5 to 7 month and 40-45%;  and P4 = 25 to 27 month and 40-45%), while (iii) vegetatif conservation treatment was used as sub plots consisting three levels, i.e T1 = cacao with disc clearing, T2 = dry field rice and soybean rotation within cacao plants, T3 = T2 + Arachis pintoi as strip plant.  There was not interaction between both cacao plant and slope treatment  with vegetatif conservation treatment to value of C factor and soil erosion.  The value of  C factor in cacao plant and slope treatment P3 (0,43) was significantly different with P4 (0,37). The value of C factor in the vegetatif conservation treatment T1 (0,25) was significantly lower (P < 0,05) than T2 (0,55) and T3 (0,39).  Soil erosion in cacao plant and slope treatment P2 (15,99 ton.ha-1.year-1) was significantly lower than P1, P3, and P4.  Furthermore, soil erosion in the vegetatif conservation treatment T1 (12,95 ton ha-1 year-1) was significantly lower than T2 and T3.  Data analysis with ANOVA (analysis of variance) and Duncan Multiple Range Test (P < 0,05) were done by using SAS program.   Key words: cacao, erosion, the value of C factor